1991
DOI: 10.1111/j.1439-0507.1991.tb00807.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungal infection as a cause of skin disease in the Eastern Province of Saudi Arabia: tinea corporis and tinea cruris

Abstract: Summary. In the period between April 1984 and April 1988 a total of 4,294 clinically suspected cases of dermatomycoses were examined for causative fungi. Of these cases 768 (17.9%) were suspected as tinea corporis (427 cases) and tinea cruris (341 cases). Twenty two different nationalities were represented. Both sexes were involved and the age range was 19 days to 70 years. Of the 768 patients examined, 738 (96.1%) had their diagnosis confirmed by direct microscopy and in 631 of these positive cases the etiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Microsporum canis was also a frequently isolated dermatophyte (Table 3), and our findings are in agreement with earlier studies from the Eastern province of Saudi Arabia, including Dammam 17 and Qatif, 18,37 which showed a high prevalence of M. canis . M. canis has also been reported as the most common pathogen producing scalp infection in children in Europe and Thailand 12,38 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Microsporum canis was also a frequently isolated dermatophyte (Table 3), and our findings are in agreement with earlier studies from the Eastern province of Saudi Arabia, including Dammam 17 and Qatif, 18,37 which showed a high prevalence of M. canis . M. canis has also been reported as the most common pathogen producing scalp infection in children in Europe and Thailand 12,38 .…”
Section: Discussionsupporting
confidence: 92%
“…Studies aimed at determining the intensity and nature of SFIs in different regions of the world are important for the prevention and management of SFIs 1,13–16 . Although SFIs are quite common in Saudi Arabia, 17,18 very little attention has been paid to their characteristics and prevalence in this country.…”
Section: Introductionmentioning
confidence: 99%
“…and Aspergillus spp. They can be transmitted from person to person in various human habitats and also from animals to human especially in children [19,20] . Several studies conducted worldwide, demonstrated that dermatophytes still the most frequent etiologic agents of skin, nail and hair fungal infections diagnosed [21] .…”
Section: Discussionmentioning
confidence: 99%